Usability, interactivity and cognition of a multicampi University website - Barcellos, Lívia Inglesis [UNESP]; Botura, Galdenoro [UNESP]; Barcellos, Ekaterina Emmanuil Inglesis [UNESP]; Barcellos, Eric Inglesis (Springer Nature, 2019)
Universities’ websites operate as channels of efficient communication with society, providing essential information for the community. However, if they do not present a suitable user interface design (UI) or user interface engineering that expedites its own comprehensibility, they damage the brand and the image of the institution. This article presents an analysis of the website of a famous Brazilian multicampi University, using Nielsen and Molich method, to identify the factors that influence the cognition and the effective interactivity of the subjects. The methodology adopted made use of an online questionnaire, totalizing 40 respondents, in which the results indicated that, at least, half of the participants face difficulties to find basic information, and about 2/3 report problems when accessing specific pages to locate the desired information contained in the sites, indicating the need for changes and adjustments.
Keywords: Heuristics; Usability; Websites